Formation of macrocyclic lactones in the Paternò–Büchi dimerization reaction - Arimura, Junya; Mizuta, Tsutomu; Hiraga, Yoshikazu; Abe, Manabu (Beilstein Journal of Organic Chemistry, 2011)
Furan-2-ylmethyl 2-oxoacetates 1a,b, in which the furan ring and the carbonyl moiety were embedded intramolecularly, were synthesized from commercially available furan-2-ylmethanol and their photochemical reaction (hν > 290 nm) was investigated. Twelve-membered macrocyclic lactones 2a,b with Ci symmetry including two oxetane-rings, which are the Paternò–Büchi dimerization products, were isolated in ca. 20% yield. The intramolecular cyclization products, such as 3-alkoxyoxetane and 2,7-dioxabicyclo[2.2.1]hept-5-ene derivatives, were not detected in the photolysate.
Keywords: furans; macrocyclic lactone; oxetane; Paternò–Büchi reaction; photochemical reaction